Poor glycemic control as a reason for referral of diabetes patients to specialists in Israel - Yacov Fogelman; Khaled Karkabi; Margalit Goldfracht (Greater Baltimore Medical Center, 2016)
Aims/introduction: Family physicians face the dilemma of when to refer patients with diabetes to specialists. This study examined attitudes of family physicians to referring patients with poor glucose control to diabetes specialists. Materials and methods: At continuous medical education courses, family physicians were asked to respond anonymously, as to whether they generally manage the diabetes of their patients, and specifically those with poor glycemic control (HbA1c>9.0%). Results: Of 470 respondents, 426 (90%) reported that they generally manage their patients' diabetes; 202 (43%) reported that they manage the diabetes of patients with HbA1c>9.0%. Board certification in family medicine and affiliation to a health maintenance organization, but not sex, age, years of professional experience, or the proportion of patients with diabetes at their clinics, were associated with referral practices. Conclusions: Family medicine residency and organizational support appear to promote treatment by family physicians of patients with poorly controlled diabetes in the primary care setting.